2008
DOI: 10.1029/2007ja012897
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric annual asymmetry observed by the COSMIC radio occultation measurements and simulated by the TIEGCM

Abstract: [1] Average F 2 -layer electron densities at December solstice are higher than those at June solstice. This phenomenon, which is often called the F 2 -layer annual asymmetry, has been observed for several decades, but its causes are still not fully understood. This study investigates global variations of this annual asymmetry observed from one year of the Constellation Observing System for Meteorology, Ionosphere and Climate (COSMIC) ionospheric radio occultation (IRO) measurements. The IRO observations show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
144
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(155 citation statements)
references
References 25 publications
10
144
0
1
Order By: Relevance
“…One of which is the definition of winter and summer and how the winter anomaly can interact with the annual anomaly, which apparently has a different source [e.g., Zeng et al, 2008]. If winter and summer values of N m F 2 are those measured at one station, then the annual anomaly cannot be uniquely separated from the differences due to a seasonal anomaly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of which is the definition of winter and summer and how the winter anomaly can interact with the annual anomaly, which apparently has a different source [e.g., Zeng et al, 2008]. If winter and summer values of N m F 2 are those measured at one station, then the annual anomaly cannot be uniquely separated from the differences due to a seasonal anomaly.…”
Section: Discussionmentioning
confidence: 99%
“…Burns et al [2012] suggested that this problem should be addressed by defining the winter anomaly as being the relationship between the electron density at the F 2 peak in the winter hemisphere and the equivalent electron density at the conjugate latitude in the opposite hemisphere at the same longitude (to remove any longitudinal effects) and on the same day of the year. This definition removes contamination by the annual anomaly (or asymmetry-[e.g., Zeng et al, 2008]). …”
Section: Introductionmentioning
confidence: 99%
“…At the equator, the OH nightglow intensity at the December solstice was stronger than that at the June solstice. We calculated the asymmetry index using the method used by Zeng et al [26] to study the annual asymmetry in ionosphere, namely,…”
Section: Seasonal Variations Of Oh and O 2 Nightglowmentioning
confidence: 99%
“…The FORMOSAT-3 is a scientific satellite, developed by the US and Taiwan, that orbits at an altitude of approximately 500 km. Approximately 1000-2500 ionospheric RO events registered per day by the COSMIC mission have been used to study the various ionospheric phenomena (e.g., He et al, 2009;Liu et al, 2008, Luan et al, 2008Potula et al, 2011;Yue et al, 2010;Zeng et al, 2008). For ground-based observations, we used data from Ascension Island (345.6 • E, 8.0 • S) located in the low latitudes area in the Southern Hemisphere.…”
Section: Introductionmentioning
confidence: 99%